Automatic creation of informative TV videos to be delivered through iTV: a system architecture - Silva, Telmo
Nowadays most of societies are facing ageing phenomenon what makes the promotion of seniors’ independence and autonomy a main issue. In this scope, one of the main factors that allow seniors to stay independent is their information level, which can be leveraged by an adequate use of Television, since this medium plays a crucial role as their key information source. In Portugal, seniors tend to spend about 5 hours per day watching TV. Thus, TV can promote the info-inclusion of seniors through the exhibition of informative contents about specific subjects enabling them to support daily decision-making processes. In this context, this article presents a system architecture to create automatically audio-visual content about public and social services and to deliver it through an interactive TV infrastructure. This paper aims to address the key aspects of the architecture and to discuss the issuesthat should be considered during its design. The paper also discusses the architecture test plan